Giant Prolactinomas: Outcomes of Multimodal Treatments for 42 Cases with Long-Term Follow-Up - Lv, Liang; Hu, Yu; Yin, Senlin; Zhou, Peizhi; Yang, Yuan; Ma, Weichao; Zhang, Shizhen; Wang, Xiujie; Jiang, Shu (Experimental and Clinical Endocrinology & Diabetes, 2019)
Giant prolactinomas represent a rare entity of pituitary tumors so that the management of these patients is still a prevalent challenge at present. Paying special attention to the treatment strategy and outcomes, we presented a large series of 42 cases looking forward to share our understanding and experience in management of these patients. Male patients accounted for 71.4% of this series and were relatively younger (35.70±2.42 vs. 52.00±3.55 years, p=0.0011) and harbored bigger tumors (14.57 vs. 7.74 cm3, p=0.0179) compared to females. Almost all of these tumors showed suprasellar extension (97.6%) and cavernous sinus invasion (92.9%). Dopamine agonist represented an efficient method to control PRL concentrations (98.8%) and reduce tumor burdens (81.2 %). PRL normalization was detected in 13 out of the 27 patients initially treated with bromocriptine (BRC) whereas none of the 14 patients with first-line operation gained a normalization of PRL concentration after surgery. Although there was no reliable predictor of tumor response, First PRL reduction was a predictive criterion for the nadir PRL level during the long-time period of follow-up for first-line bromocriptine treatment. In conclusion, patients with giant prolactinomas did not gain more benefits from initial surgery. Dopamine agonist (BRC) should be first-line treatment for giant prolactinomas whereas operation merely served as a remedy for acute compression symptoms and dopamine agonist resistance. Consecutive monitoring of serum PRL levels in the early stage of initial BRC treatment is useful for evaluation of therapeutic effect and further therapeutic decision.
Keywords: giant prolactinoma; prolactin; dopamine agonist; bromocriptine